2018
DOI: 10.1111/jocn.14338
|View full text |Cite
|
Sign up to set email alerts
|

Radiation safety education and compliance with safety procedures—The Korea Nurses’ Health Study

Abstract: Radiation safety education for nurses and their compliance with safety procedures have seldom been discussed in South Korea. However, as nurses' safety is directly related to the quality of patient care, additional safety education should be provided for hospital nurses to minimise their occupational exposure to harmful radioactive substances in clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The literature also emphasizes that nurses are not given adequate radiation safety training, and their level of knowledge often remains poorer than that of physicians and radiologic technologists (10,20). Similarly, we found a significant part of the participants did not receive radiation safety training during their education or professional life, and the majority of those receiving such training was not satisfied with the training.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…The literature also emphasizes that nurses are not given adequate radiation safety training, and their level of knowledge often remains poorer than that of physicians and radiologic technologists (10,20). Similarly, we found a significant part of the participants did not receive radiation safety training during their education or professional life, and the majority of those receiving such training was not satisfied with the training.…”
Section: Discussionmentioning
confidence: 54%
“…In their study, Kim et al (10) showed that nurses over 40 comply more with radiation safety precautions. Partly different from the literature, our data demonstrated that young nurses had more radiation and radiation safety knowledge than experienced nurses.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, it has been observed that the instruction on radiological protection is incipient among the professionals who work in interventional radiology, resulting in the adoption of erroneous methods regarding the safe use of ionizing radiation in medical practice. 8 Additionally, there is also a low adherence of workers to the use of radiological protection garments, besides the lack of knowledge on the biological effects of ionizing radiation. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
“…Ionizing radiation composed of various wave lengths including Gamma (γ)-rays and X-rays and released in a form of energy released from atoms. Worldwide the exposure of radiation exposure for different use including medical diagnostic, nuclear medicine procedure and radiotherapies were increasing [1] . Exposure of radiation either from direct and indirect source penetrate living cells or tissue which induce and prompt oxidative stress due to overproduction of several free radicals and disturbed cellular biomolecules.…”
mentioning
confidence: 99%